A study on radiological outcomes of accelerometer based hand held navigation system in total knee arthroplasty - S., Hiranyakumar; Nadagouda, Shivaraj; Harikrishnan, Vishnu (International Journal of Research in Orthopaedics, 2020)
Background: The goal of obtaining more accurate component alignment in total knee arthroplasty (TKA) has led to the development of techniques like portable accelerometer-based handheld navigation system, computer assisted system, patient specific instrumentation. Among which hand held navigation has showed promising results for achieving accurate resection and alignment and only few studies were done to assess radiological outcome or the effective component alignment using portable accelerometer-based hand held navigation system in TKA. Methods: TKA using portable accelerometer-based hand held navigation system (Smith and Nephew- knee align) was done on 25 knees with primary osteoarthritis. Preoperative and post-operative mechanical axis and component alignments were measured using hip-to-ankle radiographs. Results: Among the femoral components, 92.0% were placed within 90°±2° to the femoral mechanical axis in the coronal and 96.0% of the tibial components were placed within 90°±2° to the mechanical axis in the coronal plane, 94.3% of the TKAs had an overall lower extremity alignment within 3° of neutral to the mechanical axis, based on postoperative hip-to-ankle radiographs. Conclusions: The degree of accuracy in positioning the femoral and tibial component in TKA using portable accelerometer-based hand held navigation system (knee align) is very much promising and is an effective intraoperative tool for reducing the proportion of outliers for component placement and thus decreasing the chances of instability and early wear and tear of the components in TKA.